2008
DOI: 10.1210/jc.2008-0305
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Prolactin as a Reliable Marker for Preeclampsia, Its Severity, and the Occurrence of Adverse Pregnancy Outcomes

Abstract: Preeclampsia is characterized by increased uPRL excretion. uPRL concentrations and their isoforms appear to be suitable markers to assess the severity of preeclampsia and occurrence of adverse outcomes. PRL and and/or its isoforms might be involved in the pathophysiology of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 30 publications
3
55
0
3
Order By: Relevance
“…PRL-V has been linked to the pregnancy-associated diseases post partum cardiomyopathy (25) and preeclampsia (21). In our investigation, the detection of PRL-V in serum samples with immunoprecipitation procedures followed by western blot analysis was either unsuccessful or not reproducible.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…PRL-V has been linked to the pregnancy-associated diseases post partum cardiomyopathy (25) and preeclampsia (21). In our investigation, the detection of PRL-V in serum samples with immunoprecipitation procedures followed by western blot analysis was either unsuccessful or not reproducible.…”
Section: Discussionmentioning
confidence: 78%
“…Investigating patients with preeclampsia, Leañ osMiranda et al reported that patients with acute renal failure exhibited higher urinary PRL concentrations and higher urinary frequencies of antiangiogenic PRLfragments than patients without diminished renal function (21). Since impaired renal function is common in patients with diabetes mellitus, increased renal elimination could explain lower systemic concentrations of PRL-V.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, urinary prolactin and their isoforms of 14 and/or 16 kDa prolactin are increased in preeclampsia patients. 27 Reuwer et al proposed a recent hypothesis for the increased co-existence of PPCM and preeclampsia based on the pathophysiology of the 2 conditions sharing the same molecular pathway. 28 The current study might suggest that hypertension in pregnancy is not causative in the development of PPCM, but that a hypertensive state and PPCM are associated with other common factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prolactin elevations occur in essential hypertension (10) and during the acute phase of coronary syndromes, ischemic strokes, transient ischemic attacks (11)(12)(13), and preeclampsia (14,15), playing a causative role in the heart failure that accompanies postpartum cardiomyopathy (16). Prolactin levels predicted major cardiovascular events in men with erectile dysfunction (17), and increased expression of prolactin receptors was found in advanced human atherosclerotic plaques (18).…”
Section: Introductionmentioning
confidence: 99%